Combining a wave tank with a robotized dry test rig for WEC evaluation (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The development of Wave Energy Converter (WEC) technologies require extensive testing. While offshore testing is preferred, this comes with high costs and is time demanding and therefore require preparation. Two alternative test methods are wave tanks and dry test rigs. The former benefits from being able to achieve a controlled wave profile in-house, but is limited in scale and to unidirectional waves. The later can be constructed for larger scale and higher motion flexibility, but is limited by the accuracy of the integrated hydrodynamic model.An example of dry testing is the robotized dry test rig developed at Uppsala University (UU). Here a industrial robot emulate the behavior of a point-absorber buoy in different wave profiles and up to full motion freedom, by real-time hydrodynamic force modelling integrated in the robot controller. A scaled Power-Take-Off (PTO) device is placed in front of the robot and connected via a line to its outermost joint where the buoy motion is emulated. This test rig concept can for example be used for very flexible and repeatable early stage experiments. However, for more advanced operations requiring very high correlation with offshore operation, the accuracy of the hydrodynamic force modeling might not be sufficient.This work introduce a new WEC testing setup, combining wet buoy experiments with dry robotized testing. The conceptual idea is to have a point-absorber buoy deployed offshore or in a wave tank, with the buoy connected via a line to a real-time controlled general damper/brake device imitating PTO operation. A camera vision system supervise the buoy motion which is repeated by the robot in real-time at the robot test site. The robot is connected via a line to the PTO prototype to be tested, supervising the PTO line damping force which is repeated by the brake/damper in real-time at the buoy test site.Compared to pure dry test rigs, the proposed setup is not dependent on a numerical hydrodynamic model, as the hydrodynamic response comes directly from the buoy motion. It is on the other hand a more expensive setup with doubles sites and also restricted to the wave profiles at the buoy site. Compared to pure wave tank experiments, the proposed setup does not require the PTO to be transported and installed at a basin facility and the PTO can be tested in advance with passive robot motions, enabling more efficient wave tank utilization. Depending on the damper/brake design, the use of pulleys between with the line can also be eliminated. Compared to offshore experiments, the proposed setup makes it much easier to adjust and evaluate different PTO designs.This paper outline, demonstrate, discuss and suggest future work for the proposed novel combined wave tank and robotized dry test rig concept. An experimental setup consisting an industrial robot with an integrated force sensor and a wave tank setup with a scaled buoy-damper system and an integrated camera vision system available at UU is used, see Figure 1.